Análisis de la Influencia familiar en el rendimiento académico de los estudiantes de quinto grado de una Institución Educativa de Riohacha (2023)
The main purpose of this research project is to: Describe the family influence on the academic performance of fifth grade students of an Educational Institution in the special, tourist and cultural District of Riohacha which was carried out through an investigation with a quantitative approach of a descriptive interpretive type as an instrument, a structured questionnaire applied to 32 students and parents was used. of families who participated voluntarily. In the main results it can be indicated that 34.0% of the students declare that their family member is made up of: Parents and children, that is, of a nuclear type; but for various reasons parents are not present which influences their school performance, 46% of schoolchildren state that most of the time their family does not help them to carry out the academic activities that are reflected in their results, in addition to 52 % of students are sometimes punished when they get bad grades and 22% are always punished. With the results obtained, it can be said that the family directly influences the school performance of the students, specifying that if there is a significant affectation